Pemberdayaan Masyarakat melalui Pelatihan Budidaya Lebah Klanceng untuk Ketahanan Ekonomi dan Konservasi Lingkungan - Arsyad, Mufid; Haqiqi, Nurul Azizah; Fajri, Muhammah Niki Faza Nur; Lestari, Restu; Ristiana, Rina; Putri, Leni Diyana; Febriani, Lia Putri; Rohmah, Siti Nur; Irawan, Piki Anderi; Nurrohman, Deni; Masri, Masri; Aprizal, Aprizal; Alensa, Rizki; Irawan, Sukma; Nugraha, Iqbal; Apriyanto, Nanang (CV. Edutechnium Indonesia, 2025)
Stingless bees (Tetragonula laeviceps), commonly known as Klanceng honey bees, have significant ecological and economic value. Their role in pollination contributes to biodiversity conservation, while their honey has high market potential due to its medicinal properties. This community service program aims to introduce and develop sustainable stingless bee farming among local communities as an alternative source of income. The activities include theoretical and practical training on colony management, hive maintenance, honey extraction, and product marketing. Participants are also educated on the ecological benefits of stingless bee conservation to promote environmental awareness. The results of this program indicate a positive response from the community, with increased knowledge, skills, and motivation to engage in stingless beekeeping. By fostering sustainable beekeeping practices, this initiative is expected to enhance local economic resilience while contributing to environmental preservation.